Urbanisation accelerates carbon cycling and greenhouse gas emissions along a river-ocean continuum in the humid subtropics - Ho Wen Lo; Henry Charles James Thomas; Nga Man Chung; Jiao Liu; Qianqian Yang; Benoit Thibodeau; Lishan Ran (Environmental Research, 2026)

Microbial Ecology of Mixotrophic Chain Elongation: Megasphaera spp. as Drivers of Medium‐Chain Carboxylate Production From H 2 , CO 2 , and Carboxylates - Grégoire B. L. Henry; Julien Tremblay; Benoit A. Stenuit; Patrick A. Gerin (Environmental Microbiology, 2026)
The production of medium‐chain carboxylates (MCC) by mixed culture fermentation of complex organic feedstocks is often constrained by the availability of reducing equivalents. Therefore, mixotrophic fermentation processes, which integrate diverse carbon and reducing equivalents sources, are gaining more attention. However, the microbial communities evolving in such complex environments, where organic and inorganic substrates interact, remain insufficiently understood. To identify the key microorganisms involved in mixotrophic MCC production, two bioreactors were initially fed with brewer's spent grain as organic feedstock and supplemented daily with H 2 and CO 2 as inorganic substrates. Time‐course analyses of net metabolite production rates and microbial community composition identified Megasphaera spp. (likely M. elsdenii and M. hexanoica ) as the main chain elongators in the system. The results suggest that these Megasphaera species metabolize short‐chain carboxylates, H 2 and CO 2 , with potential cross‐feeding interactions with acetogens (likely Clostridium ljungdahlii and Clostridium luticellarii ). The homoacetogenic acetate produced is subsequently elongated, likely by Megasphaera species, using H 2 and CO 2 as electron and carbon sources for production of elongated carboxylates. This study paves the way for the development of MCC production strategies that integrate organic waste valorization with direct CO 2 utilization, using H 2 as an electron donor, a process that aligns with low‐carbon‐footprint technologies.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Habitat suitability model for identifying human-wildlife interface and implications for wildlife trade of Sunda pangolin in Borneo - Chrishen R. Gomez; Caroline C. Sartor; David W. Macdonald; Paul J. Johnson; Benoit Goossens; Elisa Panjang; Penny C. Gardner; Nicola K. Abram; Roshan Guharajan; Seth T. Wong; Jaffly Jubili; Jasrin Kuntagil; et al. (Environmental Monitoring and Assessment, 2026)
Pangolins are the most trafficked mammals in the world. Sunda pangolins ( Manis javanica ), in particular, are critically endangered due to their proximity to consumption hotspots and the scale of the globalized illegal trade network. Data on their ecological drivers can inform targeted strategies to cauterize supply lines. We used data from 1455 camera-stations deployed between 2008 and 2024 across a heterogeneous mix of landscapes in Sabah, northern Borneo, to model the geomorphological and anthropogenic drivers of Sunda pangolin distribution. Our most parsimonious logistic regression model included six variables: accessibility to human population ( β = 0.597, p = 0.004), soil cation exchange capacity ( β = −0.665, p = 0.003), soil clay content ( β = −0.311, p = 0.051), soil nitrogen concentration ( β = 0.9862, p = 0.0001), soil bulk density ( β = 0.43, p = 0.143), and topographic position index ( β = −0.61, p = 0.005). The model performed well as evaluated using an out-of-sample test dataset (sensitivity = 0.89, specificity = 0.57, and AUC = 0.73). A high proportion (~ 43%) of rural, human-dominated areas were identified as highly suitable pangolin habitat, but only ~ 15% of these areas are protected. We further confirmed the overlap in highly suitable pangolin habitat and human-occupied land using an independent citizen science dataset of pangolin detections collected between 2019 and 2024 (Boyce index = 0.75). Our results illustrate that Sunda pangolins often live in high-risk areas but also suggest an opportunity to develop community-centered conservation strategies to curb poaching and cauterize supply lines fueling the trade of Sunda pangolins in Southeast Asia.

A half-century of nuclear research, education and training: Story of the JSI TRIGA reactor - Luka Snoj; Klemen Ambrožič; Loïc Barbot; Ljudmila Benedik; Arne Bratkič; Ivana Capan; Christelle Reynard-Carette; Vladimir Cindro; Dušan Čalič; Christophe Destouches; Benoit Geslot; Alireza Haghighat; et al. (Annals of Nuclear Energy, 2025)

Tidal currents and atmospheric inorganic nitrogen contribute to diurnal variation of dissolved nutrients and chlorophyll a concentrations in Mirs Bay, Hong Kong - Ho Wen Lo; Xu Yu; Hanzhe Chen; Wai Ching Chu; Nga Man Chung; Sze Wing Lau; Jinjian Li; Shumin Liang; Kezheng Liao; Henry Charles James Thomas; Ziyan Wang; Zijing Zhang; et al. (Regional Studies in Marine Science, 2025)

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

The multilevel society of proboscis monkeys with a possible patrilineal basis - Ikki Matsuda; Tadahiro Murai; Cyril C. Grueter; Augustine Tuuga; Benoit Goossens; Henry Bernard; Nurhartini Kamalia Yahya; Pablo Orozco-terWengel; Milena Salgado-Lynn (Behavioral Ecology and Sociobiology, 2024)
Multilevel societies (MLS), which are characterized by two or more levels of social organization, are among the most complex primate social systems. MLS have only been recorded in a limited number of primates, including humans. The aim of this study was to investigate whether proboscis monkeys ( Nasalis larvatus ) form MLS in Sabah, Malaysia, and to genetically characterize their dispersal patterns. Association data were obtained through direct observation (35 months) and kinship data through genetic analysis, based on feces collected from ~ 200 individuals. The results strongly suggest that proboscis monkeys exhibit a form of MLS, with several core reproductive units and a bachelor group woven together into a higher-level band. Genetic analysis revealed that the females migrated randomly over short and long distances; however, the males tended to migrate relatively shorter distances than females. Furthermore, male-male dyads showed a slightly higher average relatedness than female-female dyads. Combined with the results of direct observations, we conclude that proboscis monkeys form MLS with at least two layers and a patrilineal basis. Since patrilineal MLS have been identified as an important step in the evolution of human societies, their convergent appearance in proboscis monkeys may help us understand the drivers of human social evolution. Significance statement The aim of this study was to determine the social organization of proboscis monkeys by direct observation and genetic analysis. The results revealed that their social system exhibited a form of multilevel society with a possible patrilineal basis. Since humans exhibit a similar constellation of social features, proboscis monkeys may offer insightful clues about human social evolution.

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Modelling the creep behaviour and induced failure of clay rock from microscale viscosity to large-scale time-dependant gallery convergences using a multiscale numerical approach - Yufeng Sun; Benoit Pardoen; Henry K.K. Wong (Computers and Geotechnics, 2023)

Hydrogeochemical processes of critical zone developed in Tégulines Clay, Paris Basin: Hydrogeochemical and multi-isotopic approach (δ13C, δD, δ18O, 87Sr/86Sr and 14C) - Catherine Lerouge; Mathieu Debure; Ana-Maria Fernández; Philippe Négrel; Benoit Madé; Nicolas Maubec; Christine Fléhoc; Catherine Guerrot; Michaela Blessing; Benoit Henry; Jean-Charles Robinet (Journal of Hydrology, 2023)

Circulating level of Angiopoietin-2 is associated with acute kidney injury in coronavirus disease 2019 (COVID-19) - Brandon Michael Henry; Maria Helena Santos de Oliveira; Isaac Cheruiyot; Justin L. Benoit; David S. Cooper; Giuseppe Lippi; Timothy D. Le Cras; Stefanie W. Benoit (Angiogenesis, 2021)

Effect of the processing methodology on satellite altimetry-based global mean sea level rise over the Jason-1 operating period - Olivier Henry; Michael Ablain; Benoit Meyssignac; Anny Cazenave; Dallas Masters; Steve Nerem; Gilles Garric (Journal of Geodesy, 2014)

Past and Future Impact of Deep Drilling in the Oceanic Crust and Mantle - Henry Dick; James Natland; Benoit Ildefonse (Oceanography, 2006)